2003
DOI: 10.1002/jsfa.1437
|View full text |Cite
|
Sign up to set email alerts
|

The use of mechanical analyses, scanning electron microscopy and ultrasonic imaging to study the effects of high‐pressure processing on multilayer films

Abstract: The effects of high-pressure processing (HPP) on the mechanical and physical characteristics of eight high-barrier multilayer films were investigated. These films were PET/SiO x /LDPE, PET/Al 2 O 3 /LDPE, PET/PVDC/nylon/HDPE/PP, PE/nylon/EVOH/PE, PE/nylon/PE, metallised PET/EVA/LLDPE, PP/nylon/PP and PET/PVDC/EVA. In addition, PP was evaluated as a monolayer film for comparison purposes. Pouches made from these films were filled with distilled water, sealed, then pressure processed at 600 and 800 MPa for 5, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 21 publications
2
28
0
1
Order By: Relevance
“…Scanning acoustic microscopy (C-SAM) has been utilized as an alternative to provide subsurface information on various plastics. C-SAM can detect, classify, and accurately produce an image of opaque materials using ultrasonic waves ranging from 5 to 500 MHz by means of a pulsed focused beam in a raster pattern over a sample [8]. This technique can show changes in elastic properties occurring between two constituents in a multilayer structure or within one constituent.…”
Section: Other Testing Approaches For Evaluation Of Hpp Effects On Pamentioning
confidence: 98%
See 3 more Smart Citations
“…Scanning acoustic microscopy (C-SAM) has been utilized as an alternative to provide subsurface information on various plastics. C-SAM can detect, classify, and accurately produce an image of opaque materials using ultrasonic waves ranging from 5 to 500 MHz by means of a pulsed focused beam in a raster pattern over a sample [8]. This technique can show changes in elastic properties occurring between two constituents in a multilayer structure or within one constituent.…”
Section: Other Testing Approaches For Evaluation Of Hpp Effects On Pamentioning
confidence: 98%
“…Delamination, detachment, cracks and folds are indirectly associated with increased permeation rates of aroma compounds such a p-cymene [16]. By means of SEM, Caner et al [8] identified small wrinkles in packaging materials PET/Al 2 O 3 / LDPE, PET/SiO x /LDPE and PET/PVDC/4%EVA/LLDPE after HPP (800 MPa and 45°C), showing that physical integrity was not affected. However, numerous fold and wrinkles were seen on the food contact layer of a MET-PET material, making it not suitable for HPP.…”
Section: Other Testing Approaches For Evaluation Of Hpp Effects On Pamentioning
confidence: 98%
See 2 more Smart Citations
“…Unos de los factores más importantes que han contribuido al éxito de los envases plásticos es la posibilidad de utilizar estructuras multicapa. Dicho complejo multicapa, adecuado para preenvasar alimentos que van a ser tratados con altas presiones, debe de poseer la suficiente flexibilidad, elasticidad y resistencia a delaminación durante el proceso de compresión, ya que la pérdida de integridad estructural puede implicar un deterioro en la calidad y seguridad del alimento envasado 25 .…”
Section: Tratamiento Con Altas Presiones Hidrostáticasunclassified